Free energy of the uniform electron gas: Testing analytical models against first‐principles results1. Issue 3 (4th April 2017) - Groth, Simon; Dornheim, Tobias; Bonitz, Michael
Abstract : The uniform electron gas is a key model system in the description of matter, including dense plasmas and solid‐state systems. However, the simultaneous occurrence of quantum, correlation, and thermal effects makes the theoretical description challenging. For these reasons, over the last half century, many analytical approaches have been developed, the accuracy of which has remained unclear. We have recently obtained the first ab initio data for the exchange correlation free energy of the uniform electron gas, which now provides the opportunity to assess the quality of the mentioned approaches and parameterizations. Particular emphasis is placed on the warm, dense matter regime, where we find significant discrepancies between the different approaches.